Oct2 and Obf1 as Facilitators of B:T Cell Collaboration during a Humoral Immune Response - Corcoran, Lynn M.; Emslie, Dianne; Kratina, Tobias; Shi, Wei; Hirsch, Susanne; Taubenheim, Nadine; Chevrier, Stephane (Frontiers in Immunology, 2014)
The Oct2 protein, encoded by the Pou2f2 gene, was originally predicted to act as a DNA binding transcriptional activator of immunoglobulin (Ig) in B lineage cells. This prediction flowed from the earlier observation that an 8 bp sequence, the “octamer motif”, was a highly conserved component of most Ig gene promoters and enhancers, and evidence from over-expression and reporter assays confirmed Oct2-mediated, octamer-dependent gene expression. Complexity was added to the story when Oct1, an independently encoded protein, ubiquitously expressed from the Pou2f 1 gene, was characterised and found to bind to the octamer motif with almost identical specificity, and later, when the co-activator Obf1 (OCA-B, Bob.1), encoded by the Pou2af1 gene, was cloned. Obf1 joins Oct2 (and Oct1) on the DNA of a subset of octamer motifs to enhance their transactivation strength. While these proteins variously carried the mantle of determinants of Ig gene expression in B cells for many years, such a role has not been borne out for them by characterisation of mice lacking functional copies of the genes, either as single or as compound mutants. Instead, we and others have shown that Oct2 and Obf1 are required for B cells to mature fully in vivo, for B cells to respond to the T cell cytokines IL5 and IL4, and for B cells to produce IL6 normally during a T cell dependent immune response. We show here that Oct2 affects Syk gene expression, thus influencing B cell receptor signalling, and that Oct2 loss blocks Slamf1 expression in vivo as a result of incomplete B cell maturation. Upon IL4 signalling, Stat6 up-regulates Obf1, indirectly via Xbp1, to enable plasma cell differentiation. Thus, Oct2 and Obf1 enable B cells to respond normally to antigen receptor signals, to express surface receptors that mediate physical interaction with T cells, or to produce and respond to cytokines that are critical drivers of B cell and T cell differentiation during a humoral immune response.